East Indian Milk Seller, Trinidad, B. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2023)
Features an East Indian milk seller, Trinidad. Dressed in her Indian attire, she is bare footed and carries a small metal bucket on her head and small metal cup in her hand. This posed image appears to have been taken indoors on a carpeted floor,with a partial view of a curtain. This is a divided back postcard. Back of the postcard INTP SK £5 – (Handwritten in pencil). Muir, Marshall & Co., Port of Spain, Trinidad.
Landscape; Black & white; 3 ½” x 5 ½”
Keywords: Clothing & dress; Women; Food vendors; Milkwomen; Milk seller